Prevenção, controle e problemáticas do Capim-annoni-2 em campo nativo: percepção dos produtores do Município de Dom Pedrito, RS - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The Eragrostis plana Ness commonly known as capim-annoni-2 is invading the rangland in the Southern Brazil. This dissemination has contributed to the native field the disappearance of species richness, as well as the reduction of forage quality of the ranglands, which feed millions of ruminants. In this sense, the present work aims to verify the perception and positioning of cattle ranchers on the invasion of capimannoni-2 grass in a native field in the municipality of Dom Pedrito, Rio Grande do Sul. For this, some points related to challenges, advances, technology insertion and failures were studied in the management of capim-annoni-2 grass, in order to understand the management strategies being conducted by the producers and their difficulties of prevention and control. The data were collected through a questionnaire containing 19 open and closed questions. The contact of the rural producers was provided by Emater (Company of Technical Assistance and Extension Rural) and Syndicate Rural of Dom Pedrito. The number of farmers was established according to the criteria of saturation of responses, totaling 18 interviewees. From the analysis of the results, it was verified that in relation to the level of infestation in the rural properties 66,7% consider the fields invaded. Most of the rural producers (88,9%) interviewed noticed changes in the landscape of the pampa biome with the entrance of the invader. In addition, 75% of the interviewees noticed differences in the animals that graze in the native field. In order to minimize the effects of capim-annoni-2 grass, 76,48% of the producers mention some management practices. Regarding what the interviewees expect in the future regarding the situation of the fields infested by the capim-annoni-2 grass, 38,89% believe that this will cause even more damage to fields and animals than benefits. Control measures that are currently available can minimize the effects of capim-annoni-2 grass in the native field when managed correctly. However, there are many points to advance in terms of prevention practices of this invader, mainly because of the lack of knowledge of these by the rural producers.
Keywords: Bioma pampa; Pecuária; Plantas invasoras; Manejo do campo nativo; Biome pampa; Livestock; Invasive plants; Native Field management; CNPQ::CIENCIAS AGRARIAS